Characteristics of Turbulent Confined Jets during Fast Filling of H2 Tank at High Pressure. Issue 5 (October 2013) - Setoguchi, T.; Alam, M.M.A.; Monde, M.; Kim, H.D.
This paper presents computational fluid dynamics (CFD) studies on turbulent confined jets of H2 gas during fast filling of a cylindrical tank at high pressure. The CFD model is validated by comparison with experimental results. An attempt is made to study the thermo-fluid dynamics of hydrogen gas alongside the characteristics of confined jets in the tank during filling. A pressure-velocity coupling algorithm is applied to solve the Favre averaged Navier-Stokes equations with an SST k -ω turbulence model. The real gas model using Redlich-Kwong equation of state is considered for density computation to model compressibility effects at high pressure. Convective heat transfer from the compressed gas to tank wall is estimated through the coupling between the energy equations of gas and solids. A standard type III, 74L hydrogen cylinder composed of aluminum and CFRP for liner and laminate is used in the present study.